An Analysis of a Partial Temporary Immunity SIR Epidemic Model with Nonlinear Treatment Rate - Saba et al. (مجلة بغداد للعلوم)
A partial temporary immunity SIR epidemic model involv nonlinear treatment rate is proposed and studied. The basic reproduction number  is determined. The local and global stability of all equilibria of the model are analyzed. The conditions for occurrence of local bifurcation in the proposed epidemic model are established. Finally, numerical simulation is used to confirm our obtained analytical results and specify the control set of parameters that affect the dynamics of the model.